Simultaneous thoracoscopic resection for coexisting pulmonary and thymic lesions - Lin, Feng (J Thorac Dis, 2015)
BACKGROUND: The management of synchronous thymic and pulmonary lesions remains a challenge due to the lack of case series and surgical guidelines. This study aims to retrospectively review our preliminary experience and results of performing simultaneous thoracoscopic resection of coexisting diseases of the lung and thymus. METHODS: Simultaneous thoracoscopic resection was performed to remove coexisting thymic and pulmonary lesions in nine patients from August 2008 to November 2013. Patient demographics, preoperative assessment, surgical procedures and postoperative course of these patients were reviewed. RESULTS: There were four female and five male patients between 43 and 70 years old (median age, 64 years). Each patient had thymic neoplasm and solitary pulmonary lesion on chest computed tomography (CT) scan. Four patients underwent thoracoscopic lobectomy and thymectomy. One patient had thoracoscopic bronchovascular sleeve lobectomy combined with thymic cyst resection (TCR). The other four patients received pulmonary wedge resection and thymectomy (n=3)/TCR (n=1). The operation lasted from 35-480 min (median, 110 min). Intra-operative blood loss was 20-380 mL (median, 120 mL). Two patients developed post-operative pneumonia without mortality. All the patients were discharged home within 9 days after surgery. Two patients died from metastatic lung cancer 14 months after surgery. CONCLUSIONS: Simultaneous thoracoscopic resection of coexisting pulmonary and thymic lesions is safe and feasible in selected patients.